Associations Between Oncology Outreach and Patient‐Sharing Measures of Care Coordination - Bruno T. Scodari; Andrew P. Schaefer; Nirav S. Kapadia; A. James O'Malley; Erika L. Moen (Cancer Medicine)
ABSTRACT Background Oncology outreach is a common strategy for addressing cancer workforce shortages, where traveling oncologists commute across clinical settings to extend their services. Despite its known benefits specifically for rural patients, oncology outreach reallocates physician resources to satellite clinics and may negatively impact the coordination of cancer care. Methods In this retrospective study, we identified patients with incident breast, colorectal, and lung cancers from 2016–2019 nationwide Medicare claims and linked them to oncologists using Part B. We considered encounters occurring outside the physician's primary hospital service area as “outreach visits” and calculated the proportion of outreach visits by oncology specialty for contiguous US hospital referral regions (HRRs) using 2016–2017 claims. We constructed a nationwide physician patient‐sharing network from 2018–2019 claims and computed median care density—a measure of physician team familiarity—and local transitivity—a measure of physician cohesion/clustering—for each HRR as proxies for care coordination. Generalized linear models were used to explore the associations between oncology outreach and care coordination measures at the HRR level. Results We found that HRRs with high medical oncology outreach were associated with 16% decreases in care density (95% CI: 5–25) and 4% decreases in local transitivity (95% CI: 1–8) compared to HRRs with low medical oncology outreach. HRRs with high radiation and surgical oncology outreach were not associated with network‐based measures of care coordination. Conclusions While medical oncology outreach increases access for underserved patient populations, it potentially fragments care delivery across clinical settings. Health systems may consider this trade‐off to inform decisions concerning the implementation of outreach programs or policies aimed at hedging against fragmentation in markets with active outreach arrangements.